Managing attendance at work: the role of line managers in the UK grocery retail sector. Issue 4 (1st June 2015) - Keith Townsend; Professor Tony Dundon, Dr; Hadjisolomou, Anastasios
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the role of line managers in managing attendance at work in the lean regime of grocery retailing. The increasing competitiveness within the sector, coupled with the sophisticated control systems in place put pressure on managers to keep labour costs low. Attendance, therefore, becomes a critical factor, particularly as staffing levels become leaner. Taking this into account, it is necessary to understand the parameters of the line managers' role in managing attendance, especially within the lean food retail market and the antagonistic terrain of the supermarket shop floor. The paper discusses the impact of lean retailing on line managers' authority and provides a fresh sociological analysis regarding their role in managing attendance, offering insights into managerial practices on the UK supermarket shop floor. Design/methodology/approach – The paper draws on qualitative research evidence from two case study grocery retail organizations in the UK. It reports on 44 semi-structured interviews and provides a multi-level analysis aiming to understand the different perspectives on the problem examined. Findings – The paper reveals the existence of a centralized absence management policy and highlights the greater involvement of line managers in this procedure. Line managers though were subjected to forces of bureaucratic control, intensification and degradation of their work. Despite having an active role within the attendance management process and high responsibility for the implementation of rules and procedures handed down by head office, they had limited authority over the process. Line managers perceived the latter as routine and a box-ticking exercise and had developed coping tactics to deal with the control from above. Originality/value – This paper provides practical and theoretical considerations over the role of line management in the labour process, investigating their role in managing attendance at work within the lean terrain of food retailing. This research contributes to the ongoing academic discussions related to the devolvement of HR responsibilities to the line, highlighting the great involvement of line managers in the absence policy. It also provides a sociological perspective over line managers' authority and discretion in managing attendance, revealing that they were subjected to direct and bureaucratic control within their role in attendance management. However, the research reveals that line managers were not passive in the face of direct control from above and had developed tactics to cope with the monotony and the repetition of this process, attempting to somehow escape the top-down control they were subjected to.